Methodology devising for bucket-wheel excavator surveying by laser scanning method to determine its main geometrical parameters - Vrublová, Dana; Kapica, Roman; Jurman, Josef (Geodesy and Cartography, 2012)
The application of laser scanning techniques to bucket-wheel excavator surveying seeks primarily to determine the machines’ key geometric parameters and to establish realistic mathematical descriptions of their movement dynamics in 3D space. The data will be used to visualize excavator movement and to control the coal extraction process in real time. The measurements take place at Doly Nástup Opencast Coal Mine, Tušimice, North-Bohemian Lignite Coal Field, Czech Republic. GNSS technology and inclinometric measurements are used to calculate 3D positions of the bucket-wheel excavators. The data is transferred to the research team workplace and stored in a database. KVAS software is used to visualise the bucket-wheel excavators and their 3D movements in real time.